THE THEORETICAL DESCRIPTION FOR 4-NITROQUINOLINE- N-OXIDE ELECTROCHEMICAL DETERMINATION ON V(OH)2- MODIFIED ELECTRODE. - Романів, Людмила Вікторівна (Applied Journal of Environmental Engineering Science., 2021)
In this work, the possibility of use of vanadium (II) dioxide as an electrode modifier for the cancer marker 4-nitroquinoline-N-oxide has been made. Two parallel mechanisms of assisted electroanalytical determination are possible, due to the presence of peroxide group and nitric group. Both of them provide the electrode reversibility, due to the formation of V(IV) and V(III) compounds. In both of the cases, the electroanalytical process is efficient. On the other hand, the oscillatory behavior probability in this system is correspondent to the electroanalytical process with sequent or parallel electrochemical stages.
Keywords: electrochemical sensors, 4-nitroquinoline-N-oxide, vanadium dioxide, chemically modified electrodes, stable steady-state.